Infoinclusão: uma categoria de análise para a ciência da informação nas perspectivas do diálogo e da participação - Miriam Gontijo de Moraes (2005)
Among the reasons for the existence and evolution of the Information Science is its connection with information technology and the problems brought forth by it. It is assumed that in the context of the Technological Imperative, characterized by the transformations brought forth the society of information, the Information Science plays and will go on playing a role, highlighted in that scenario, by the social and human dimension, that the research in that field has acquired along its path, which goes beyond the merely technological dimension. The challenge of spreading access to the huge store of information and knowledge continuously growing with the use of the technologies of information has met with new problems, among which is the risk of engendering the post-modern barbarism, identified as infoexclusion. The main contribution of this research to the Information Science is to support the concept of Infoinclusion as an analytic category in order to facilitate a review of the condition of the technological imperative of an emerging information society that places us either in the threshold of barbarism or facing the construction of a public sphere, based on agreement and mutual understanding. The theoretical foundation of the Infoinclusion concept was based on the new critical and autonomous reasoning coined by Habermas as the communicative reasoning. According to Habermas's perspective, to produce knowledge doesn't limit itself to verifying, but also includes inquiring and building the future, approaching truth as a claim to validity, for which the only guarantee of acceptance in society is the possibility of questioning and being questioned. Being subject to discussion is thus the scientific criterion, it can only be scientific if it is debatable. In the political plan and in relation to the increasing of citizenship, participation will depend more and more on communication among the members of a community, as a way of overcoming the limits imposed by the awareness of daily life, because as reality is a whole, to dismantle it can help to study it better, but its appropriate understanding will demand viewing it as a whole. Our empirical reference was taken from the experience of local people taking part in the management of transport and traffic in BH by means of regional committee representatives. The objective of developing the paper in that perspective was to approach infoexclusionthrough a process of intersubjective construction which resulted in the concept of Infoinclusion.